Ongoing substrate-driven atrial fibrillation “boxed” in the left atrial posterior wall with ablation: a case report - Traykov, Vassil; Marchov, Daniel; Martinov, Emiliyan; El Abbady, Asmaa; Gelev, Valeri; Dichtl, Wolfgang (Frontiers in Cardiovascular Medicine, 2023)
Patients undergoing valve surgery for rheumatic heart disease are expected to develop significant atrial arrhythmogenic substrates outside of the pulmonary veins, which sometimes require complex ablation techniques for the treatment of symptomatic arrhythmias. We describe, herein, the case of a 76-year-old male undergoing endocardial ablation for the treatment of symptomatic persistent atrial fibrillation which developed after aortic and mitral valve replacement with a simultaneous tricuspid ring annuloplasty. Following pulmonary vein isolation, the patient's atrial fibrillation was converted into cavotricuspid isthmus-dependent atrial flutter. After a successful cavotricuspid isthmus ablation, the arrhythmia reverted back to a left atrial tachyarrhythmia originating from the posterior wall. A linear left atrial lesion led to the electrical isolation of a large area, which included the posterior wall, as well as the containment of the ongoing fibrillatory activity, while sinus rhythm was restored in the rest of the atria. In conclusion, successful left atrial posterior wall isolation can be achieved in the setting of severe scarring due to previous atriotomy by creating a linear lesion on the atrial roof, in conjunction with pulmonary vein isolation, sparing the patient from requiring bottom-line ablation, and avoiding possible esophageal injury. Such compartmentalization of the left atrium may effectively contain local fibrillatory activity, while allowing for the restoration of sinus rhythm.